ChemInform Abstract: Catalytic Synthesis of 2H‐Chromenes. Issue 22 (15th May 2015) - Majumdar, Nilanjana; Paul, Nanda D.; Mandal, Sutanuva; de Bruin, Bas; Wulff, William D.
Abstract: Review: 114 refs.